MALAM TIRAKATAN PERINGATAN KEMERDEKAAN INDONESIA: Studi Living Qur’an Hadis Masyarakat Mlangi, Yogyakarta - Syihabuddin, Muhammad (Jurnal Moderasi, 2023)
Abstract The community cannot be separated from a commemoration, for example the Mlangi people with the tirakatan tradition to commemorate Indonesian independence. Tirakatan activities are wrapped in the nationalism concept and religion. Every community has its own purpose in holding certain activities or commemorations, each activity also has a certain meaning either expressly or impliedly. This paper will further discuss how the text (Al-Qur'an and Hadith) lives in the Mlangi community, especially in the tirakatan night commemoration which is held annually to commemorate Indonesian independence, as well as how the Qur'an Hadith responds to events held by the Mlangi community that do not all communities in other areas held a similar commemoration. This study uses a qualitative method with a phenomenological approach related to the tirakatan of the Mlangi people, by revealing an understanding of the tirakatan night tradition commemorating Indonesia's independence. Keywords: Tirakatan. Mlangi, Traditions, Qur'an Hadith.